2021
DOI: 10.1080/07853890.2021.1969033
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG8 sponging miR-181a-5p contributes to M1 macrophage polarization by regulating SHP2 expression in Henoch-Schonlein purpura rats

Abstract: Background Long noncoding RNAs (LncRNAs) are regulatory molecules that play important roles in various biological and pathological processes. Herein, we aimed to explore whether maternally expressed gene 8 (MEG8) promotes M1 macrophage polarization among Henoch-Schonlein purpura (HSP) rats, and to investigate the underlying mechanism. Methods Relative mRNA expression of MEG8, miR-181a-5p and suppressor of SH2 domain-containing tyrosine phosphatase 2 (SHP2) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, MEG8 involvement within HSP is yet unclear. Previously, we found that MEG8 was expressed at low levels in RMDM-enhanced M1 macrophages polarization within HSP rats [15]. Further experiments in this research demonstrated that MEG8 reverses Th17/Treg imbalance within HSP CD4+ T-cell population, thereby providing novel insights into the MEG8 mechanism of action in HSP.…”
Section: Discussionmentioning
confidence: 56%
“…Nonetheless, MEG8 involvement within HSP is yet unclear. Previously, we found that MEG8 was expressed at low levels in RMDM-enhanced M1 macrophages polarization within HSP rats [15]. Further experiments in this research demonstrated that MEG8 reverses Th17/Treg imbalance within HSP CD4+ T-cell population, thereby providing novel insights into the MEG8 mechanism of action in HSP.…”
Section: Discussionmentioning
confidence: 56%
“…However, others have reported that many of the miRNA associated with Ad14 infection can regulate inflammatory responses, ALI/ARDS and other lung inflammatory diseases. For example, increased expression of miR-181a-5p decreases NK-κB activation and alleviates inflammatory responses in COPD, whereas miR-181a-5p inhibition contributes to macrophage M1 polarization [88,89]. Increased expression of miR-27a-3p decreases expression of TNFα and IL6, while increased expression of let-7a-5p decreases expression of TNFα, IL6 and IL1β [73,90].…”
Section: Discussionmentioning
confidence: 99%
“…Characterized in a Henoch-Schönlein purpura rat model, SH2-domain-containing tyrosine phosphatase 2 (SHP2) is another potential modulator of macrophage polarization due to its inhibitory effect on the M2 polarization-promoting STAT3 signaling pathway while also actively inducing M1 polarization. Conversely, SHP2 has been considered to be a plausible target of hsa-miR-181a-5p, which could result in SHP2 under-expression and thus the disinhibition of STAT3 signaling [ 15 ]. Indeed, hsa-miR-181a-5p was among those differentially expressed in our AAV sample pool.…”
Section: Discussionmentioning
confidence: 99%